Prospects for Development of Laying Chickens in Gunung Sari District, West Lombok Regency - Maydasari, Elita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Based on the population of laying hens according to provinces in Indonesia, it shows that East Java surpasses the population of laying hens, followed by the provinces of Central Java and West Java, the island of Java surpasses the number of laying hen production because the demand for chicken eggs has increased because it is supported by the factor of the number of people who will consume eggs and processed products. eggs, therefore, West Nusa Tenggara also has prospects for developing egg-laying chicken production because it can be seen from the projected population and egg consumption which always increases every year. The risks faced by farmers are the large number of predators who prey on laying hens, chicken disease attacks, unpredictable weather due to changes in earth temperature causing many chickens to suddenly die, human resources who are less skilled in raising chickens, marketing risks, the market as a determinant of farmers' profits in producing eggs but uncertain market conditions make farmers experience losses, for example the arrival of competing eggs from outside the region such as Balinese and Javanese eggs which are larger in size with cheaper prices, making local eggs difficult in marketing and finally the financial factor, finance is an obstacle for farmers in promote livestock business.